Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Follow through with the function (x+7)²
(x+7)² is the same as (x+7)(x+7).
You get x² + 14x + 49
Plug it back into the equation to get
y=x² + 14x + 49 - 5, which equals y=x² + 14x + 44
The formula for the x point in the vertex is -b/2a. (a is x² and b is x)
So -14/2 = -7 = x
Plug this into the equation.
y=-7² + 14(-7) + 44
y=49 - 98 + 44
y=-5
(-7, -5)
I apologize for the error beforehand--I typed 49 instead of 44 and ended up with 0 instead of -5.
(x+7)² is the same as (x+7)(x+7).
You get x² + 14x + 49
Plug it back into the equation to get
y=x² + 14x + 49 - 5, which equals y=x² + 14x + 44
The formula for the x point in the vertex is -b/2a. (a is x² and b is x)
So -14/2 = -7 = x
Plug this into the equation.
y=-7² + 14(-7) + 44
y=49 - 98 + 44
y=-5
(-7, -5)
I apologize for the error beforehand--I typed 49 instead of 44 and ended up with 0 instead of -5.
If you have an equation in the vertex form [tex]y=(x-h)^2+k[/tex] the vertex is [tex](h,k)[/tex]
In your case [tex]h=-7,k=-5[/tex] so the vertex is [tex](-7,-5)[/tex]
In your case [tex]h=-7,k=-5[/tex] so the vertex is [tex](-7,-5)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.